METHODOLOGICAL CONDITIONS FOR FORMING ACMEOLOGICAL COMPETENCE IN FUTURE TEACHERS - Tuychieva Sabina Sherzodovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  explores  the  methodological  conditions  for  forming acmeological  competence  in  future  teachers.  The  study  focuses  on  the  role  of educational environment, pedagogical interaction, and individual learning trajectories in achieving professional excellence. Special attention is given to the integration of personality-oriented  education,  innovative  teaching  strategies,  and  continuous professional growth. The acmeological perspective is considered as a key framework for  enhancing  teacher  training  quality  and  ensuring  sustainable  professional development.